Neutralising antibody responses against SARS-CoV-2 Omicron BA.4/5 and wild-type virus in patients with inflammatory bowel disease following three doses of COVID-19 vaccine (VIP): a prospective, multicentre, cohort study - Liu,Z; Alexander,J; Le,K; Zhou,X; Ibraheim,H; Anandabaskaran,S; Saifuddin,M; LIN,K; Leon,M; Constable,L; Castro,Seoane R; Anand,N; et al. (EClinicalMedicine, 2023)
BackgroundPatients with inflammatory bowel disease (IBD) receiving anti-TNF and JAK-inhibitor therapy have attenuated responses to COVID-19 vaccination. We aimed to determine how IBD treatments affect neutralising antibody responses against the Omicron BA.4/5 variant.MethodsIn this multicentre cohort study, we prospectively recruited 340 adults (69 healthy controls and 271 IBD) at nine UK hospitals between May 28, 2021 and March 29, 2022. The IBD study population was established (>12 weeks therapy) on either thiopurine (n = 63), infliximab (n = 45), thiopurine and infliximab combination therapy (n = 48), ustekinumab (n = 45), vedolizumab (n = 46) or tofacitinib (n = 24). Patients were excluded if they were being treated with any other immunosuppressive therapies. Participants had two doses of either ChAdOx1 nCoV-19 or BNT162b2 vaccines, followed by a third dose of either BNT162b2 or mRNA1273. Pseudo-neutralisation assays against SARS-CoV-2 wild-type and BA.4/5 were performed. The half maximal inhibitory concentration (NT50) of participant sera was calculated. The primary outcome was anti-SARS-CoV-2 neutralising response against wild-type virus and Omicron BA.4/5 variant after the second and third doses of anti-SARS-CoV-2 vaccine, stratified by immunosuppressive therapy, adjusting for prior infection, vaccine type, age, and interval between vaccination and blood collection. This study is registered with ISRCTN (No. 13495664).FindingsBoth heterologous (first two doses adenovirus vaccine, third dose mRNA vaccine) and homologous (three doses mRNA vaccine) vaccination strategies significantly increased neutralising titres against both wild-type SARS-CoV-2 virus and the Omicron BA.4/5 variant in healthy participants and patients with IBD. Antibody titres against BA.4/5 were significantly lower than antibodies against wild-type virus in both healthy participants and patients with IBD (p < 0.0001). Multivariable models demonstrated that neutralising antibodies against